Performance, emission and combustion characteristics of a diesel engine using Carbon Nanotubes blended Jatropha Methyl Ester Emulsions - J. Sadhik Basha; R.B. Anand (Alexandria Engineering Journal, 2014)
An experimental investigation was conducted in a single cylinder constant speed diesel engine to establish the effects of Carbon Nanotubes (CNT) with the Jatropha Methyl Esters (JME) emulsion fuel. The JME was produced from the Jatropha oil by transesterification process, and subsequently the JME emulsion fuel was prepared in the proportion of 93% of JME, 5% of water and 2% of surfactants (by volume) with a hydrophilic–lipophilic balance of 10. The Carbon Nanotubes are blended with the JME emulsion fuel in the various dosages systematically. The whole investigation was conducted in the diesel engine using the following fuels: neat JME, neat JME emulsion fuel and CNT blended JME emulsion fuels accordingly. The experimental results revealed an appreciable enhancement in the brake thermal efficiency for the CNT blended JME emulsion fuels compared to that of neat JME and neat JME emulsion fuel. At the full load, the brake thermal efficiency for the JME fuel observed was 24.80%, whereas it was 26.34% and 28.45% for the JME2S5W and JME2S5W100CNT fuels respectively. Further, due to the combined effects of micro-explosion and secondary atomization phenomena associated with the CNT blended JME emulsion fuels, the level of harmful pollutants in the exhaust gases (such as NOx and smoke) was drastically reduced when compared to that of neat JME. At the full load, the magnitude of NOx and smoke opacity for the neat JME was 1282 ppm and 69%, whereas it was 910 ppm and 49% for the JME2S5W100CNT fuel respectively.